Determination of pork adulteration in roasted beef meatballs using fourier transform infrared spectroscopy in combination with chemometrics - Nurani, Laela Hayu; Kusbandari, Aprilia; Guntarti, Any; Ahda, Mustofa; Warsi,; Mubarok, Fitria Nur Aisyah; Abdul Rohman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The pork adulteration in food is a matter of concern for Muslims worldwide. This study aimed to quantitatively analyze and classify pork and beef in roasted meatballs using the Fourier Transform Infrared (FTIR) spectroscopy method combined with chemometrics. To obtain the FTIR spectral data, pure beef meatballs and beef meatballs added with pork at various concentrations were analyzed in the mid-infrared region corresponding to wavenumbers ranging from 4000 to 400 cm-1. Samples of beef meatballs randomly selected from the market were analyzed in the optimum condition in terms of wavenumbers capable of providing best modeling. Qualitative and quantitative analyses were performed on the optimum wavenumbers of 1100-900 cm-1 using chemometrics of Partial Least Square (PLS) and Principal Component Analysis (PCA), respectively. The PLS calibration model for the relationship between actual values of pork (x-axis) and predicted FTIR values (y-axis) of roasted meatballs resulted in the equation of y = 0.99965x + 0.0221, with a coefficient of determination (R2 -value) of 0.99965 and root mean square error of calibration (RMSEC) of 0.7137%. The PCA indicated differences in quadrants between pure beef and pork roasted meatballs. Most samples of marketed beef meatballs lied in the beef meatball quadrant. However, one sample of marketed beef meatballs was in the pork meatball quadrant; thus, it contained pork. To conclude, the FTIR spectroscopy method combined with chemometrics could qualitatively and quantitatively identify the ingredient of pork in roasted beef meatballs.